The role of technology acceptance model factors on purchase intention in e-commerce - Anak Agung Ayu Puty Andrina; Christian Jordan Kurniadi; Irantha Hendrika Kenang; Timotius FCW Sutrisno (BISMA (Bisnis dan Manajemen), 2022)
The number of Indonesian e-commerce users has increased in recent years.  Supported by escalated of information technology, higher mobile phone users, and online shopping trend, it continue to increase exponentially. This study aims to determine the effect of perceived usefulness and ease of use on the intention to purchase of e-commerce users, which is supported by the theory of the Technology Acceptance Model (TAM). The respondents are 338 students. This study uses Confirmatory Factor Analysis (CFA) to determine the validity and reliability of the construct and Partial Least Square (PLS) in testing the relationship between the variables. The findings depicted that perceived ease of use has a significant influence on attitude toward e-commerce and intention to purchase, attitude toward e-commerce significantly affects the intention to purchase, and perceived usefulness has a significant influence on attitude toward e-commerce, but not supported influence on intention to purchase. The managerial implication of this research is that the e-commerce companies in Indonesia can pay attention to the variables that become the factors in the acceptance of e-commerce to build and achieve better corporate goals.